Use of antimicrobials in the medical service of theGeneral-Educational Hospital "Dr. Enrique Cabrera". 2016 - Elizabeth Pereira Relis; Lino Aboy Capote; Juan Carlos Pulido Armas (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Since the conference about the rational use of drugs of the World Health Organization in 1985, this practice had been improving, especially antimicrobials, to prevent the increased of the resistance to these. Objective: To characterize the use of antimicrobials in the medical services of the General-Educational Hospital "Dr. Enrique Cabrera" in January 2016. Material and Methods: A retrospective and descriptive study of both sexes hospitalized 171 patients; older than 20 years old was performed. The medical records were reviewed to achieve the study variables and a database in Microsoft Excel was elaborated, that was analyzed, determining their absolute and relative frequencies. Results: 57.3% of patients received antimicrobial therapy, 52.1% were male, 38.7% hypertensive, 66.3% were 60 years and older, 77.5% received antimicrobials to treat infections, 82.8% of them were breathing low, 88.1% were treated with a combinations of 2 drugs and any microbiological testing of clinical suspicion was performed, in all, oralway was used, in 88.1% the intravenous via  was used and in none of the patients antimicrobial sequential therapy was performed, in 80.3 %  treatment period was 10 days, 50.6% received third generation cephalosporin and the most used was cefotaxime 97 (44.2%). Conclusions: The use of antimicrobials in hospitalized patients presented difficulties related to non-performing microbiological studies, the high use of intravenous and non-use of antimicrobial sequential therapy.   Keywords: drugs, antimicrobials, prevalence, use, prescription, hospitals, therapeutics, infection, administration via, microbiological study.